2016
DOI: 10.18805/ijare.v50i4.11253
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and seed quality of okra [Abelmoschus esculentus (L.) Moench]as influenced by harvesting stage and drying method

Abstract: The influence of harvesting stages and drying methods on fruit and seed quality of okra [Abelmoschus esculentus (L.) Moench.] cultivar Asontem was studied to determine the optimum stage of harvest and suitable drying method. The fruit length and diameter progressively increased and reached its peak at 30 days after anthesis by recording 9.50 and 2.83cm respectively and subsequently decreased slightly. The higher seed moisture content (46.5%) was obtained at the early harvesting stage (10 day after anthesis (DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Harrington (1972) had hypothesized and later supported by Ellis (2019) that maximum seed quality was attained at physiological maturity (PM), after which deterioration started and seed germination and vigour declines. This view has been observed for okra (Demir and Ermis, 2005;Bortey and Dzomeku, 2016), selected S. aethiopicum spp. (Tetteh et al, 2021) and A. edulis fruits (Kaiser et al, 2016).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Harrington (1972) had hypothesized and later supported by Ellis (2019) that maximum seed quality was attained at physiological maturity (PM), after which deterioration started and seed germination and vigour declines. This view has been observed for okra (Demir and Ermis, 2005;Bortey and Dzomeku, 2016), selected S. aethiopicum spp. (Tetteh et al, 2021) and A. edulis fruits (Kaiser et al, 2016).…”
Section: Discussionmentioning
confidence: 53%
“…During seed development, the maximum seed germination may coincide with the maximum dry matter accumulation that characterizes physiological maturity or mass maturity (TeKrony and Egli, 1997) as observed for okra (Demir and Ermis, 2005;Bortey and Dzomeku, 2016), selected Solanum aethiopicum species (Tetteh et al, 2021) and Allophylus edulis fruits (Kaiser et al, 2016). Other studies have also reported that maximum seed germination may not coincide with maximum dry matter accumulation as reported for tomato (Borges et al, 2019), pepper (Ruiz and Parera, 2017), safflower (Ramos et al, 2021) and eggplant (Demir et al, 2002).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The increments in fruit size every 3 days starting from 3 DAA until 9 DAA was approximately 60 mm for length and 5 mm for diameter signifying a rapid fruit elongation and expansion at the early stage of fruit development starting from fruit set th until the 9 day. Generally, fruit size tends to stabilize or even decrease at the end of the fructification process (Bortey & Dzomeku, 2016).…”
Section: Morphological Changesmentioning
confidence: 99%